Malignant transformation of hepatocellular adenoma: post-liver transplantation incidental diagnosis. - Silva, Renato Ferreira da (2009)
Hepatic adenoma is a rare benign tumor of the liver which usually presented as a solitary nodule. It can be often identified in women associated to the use of oral contraceptive. Clinical presentation of such tumor can be abdominal pain at the right hypochondrium. However, it is predominantly asymptomatic. As complication, hemoperitonium, secondary to tumor rupture or malignant degeneration to hepatocellular carcinoma may occur. We describe a patient on chronic oral contraceptive use who presented multiple and unresecable adenomas associated to grade III hepatic steatosis. After a two years follow-up, she had indication for liver transplantation, due to unresecable tumor associated to abdominal discomfort and poor quality of life. The explanted liver showed incidental focus of hepatocellular carcinoma in three of the multiple adenomas in the absence of increased alpha-fetoprotein and no radiological evidence of HCC. Although the liver transplantation to treat benign tumors can be considered a radical procedure, it can be a convenient option for patients with unresecable adenomas.